The role of spiritual intelligence in citizenship behaviours amongst Muslim staff in Malaysia - Alamanda, Dini T. (HTS teologiese studies, 2021)
Religion is so rich, comprehensive and complex that its different aspects exhibit differently in different perspectives and attitudes. Good employees express their opinions and beliefs honestly and participate in the organisational activities. In other words, they take actions that are not necessary but are useful for colleagues and organisations. These behaviours, called extra-role or organisational citizenship behaviours (OCB), refer to activities that are inherently spontaneous and conscious and are not directly and explicitly predicted by the organisation’s formal reward system, but generally enhance the organisation’s efficiency. The importance of such behaviours in religious and spiritual environments increases. Hence, this study aimed to determine the role of spiritual intelligence in exhibiting citizenship behaviours in the organisation. Therefore, 5000 employees of 40 manufacturing and services companies working in the education, finance, insurance and food sectors were selected by simple random sampling method as the statistical population of the study. Then, standard questionnaires were distributed amongst the participants, necessary data were collected and Statistical Package for the Social Sciences (SPSS) was used to analyse data. The results indicated a positive and significant relationship between spiritual intelligence and citizenship behaviours in organisations. Finally, the Structural Equation Model (SEM) results in linear structural relations (LISREL) showed that spiritual intelligence affects the citizenship behaviours (p = 0.68).Contribution: This article therefore contributes to the spirituality and spiritual intelligence of employees in the organisation as an aspect of religion.